Handbook of Blood Gas/Acid-Base Interpretation - Hasan, Ashfaq; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Analysis of blood gas can be a daunting task. However, it is still one of the most useful laboratory tests in managing respiratory and metabolic disorders. Busy medical students have struggled ineffectively with Hasselbach$1 (Bs modification of the Henderson equation, been torn between the Copenhagen and the Boston schools of thought; and lately, been confronted with the radically different strong-ion approach. In modern medical practice, the health provider$1 (Bs time is precious: it is crucial to retain focus on those aspects of clinical medicine that are of key importance. Adoption of an algorithm-based approach in the study of topics that are hard to understand (particularly those that are rooted in clinical physiology) can be extremely advantageous. Handbook of Blood Gas/Acid-Base Interpretation, 2nd edition, is organized in a logical sequence of flow charts that introduce concepts and gradually build upon them. This approach facilitates understanding and retention of the subject matter. Medical students, residents, nurses, and practitioners of respiratory and intensive care will find it possible to quickly grasp the principles underlying respiratory and acid-base physiology, and apply them effectively in clinical decision making.s
Keywords: Medicine; Anesthesiology; Critical care medicine; Internal medicine; Hematology; Pneumology; Medicine & Public Health; Intensive / Critical Care Medicine; Internal Medicine; Anesthesiology; Hematology; Pneumology/Respiratory System